Anticoagulation trends in adults aged 65 years and over with atrial fibrillation: a cohort study. Issue 2 (3rd August 2021) - Lund, Jenny; Saunders, Catherine L; Edwards, Duncan; Mant, Jonathan
Abstract : Objective: To describe patterns of anticoagulation prescription and persistence for those aged ≥65 years with atrial fibrillation (AF). Methods: Descriptive cohort study using electronic general practice records of patients in England, who attended an influenza vaccination aged ≥65 years and were diagnosed with AF between 2008 and 2018. Patients were stratified by 10-year age group and year of diagnosis. Proportion anticoagulated, type of anticoagulation (direct oral anticoagulant (DOAC) or warfarin) initiated at diagnosis and persistence with anticoagulation over time are reported. Results: 42 290 patients (49% female), aged 65–74 (n=11 722), 75–84 (n=19 055) and 85+ (n=11 513) years at AF diagnosis are included. Prescription of anticoagulation at diagnosis increased over the time period from 55% to 86% in people aged 65–74 years, from 54% to 86% in people aged 75–84 years and from 27% to 75% in people aged 85 years and over. By 2018, 92% of patients with newly diagnosed AF were started on a DOAC. Survivor function for 5-year persistence in patients prescribed DOAC was 0.80 (95% CI 0.77 to 0.82) and for warfarin 0.71 (95% CI 0.70 to 0.72). Survivor function for any anticoagulation at 5 years was 0.79 (95% CI 0.78 to 0.81), 0.73 (95% CI 0.72 to 0.75) and 0.58 (95% CI 0.59 to 0.64) for people aged 65–74, 75–84 and 85+ years, respectively. Conclusions: Rates of anticoagulation in AF in those aged ≥65 years have increased from 2008 to 2018, over which time period there has been a shift from initiating anticoagulation with warfarin to DOAC. Persistence with anticoagulation is higher in people on DOACs than on warfarin and in people aged <85 years.